Nomograms for predicting survival and recurrence in patients with adenoid cystic carcinoma. An international collaborative study. Issue 18 (December 2015) - Ganly, Ian; Amit, Moran; Kou, Lei; Palmer, Frank L.; Migliacci, Jocelyn; Katabi, Nora; Yu, Changhong; Kattan, Michael W.; Binenbaum, Yoav; Sharma, Kanika; Naomi, Ramer; Abib, Agbetoba; et al.
Abstract: Background: Due to the rarity of adenoid cystic carcinoma (ACC), information on outcome is based upon small retrospective case series. The aim of our study was to create a large multiinstitutional international dataset of patients with ACC in order to design predictive nomograms for outcome. Methods: ACC patients managed at 10 international centers were identified. Patient, tumor, and treatment characteristics were recorded and an international collaborative dataset created. Multivariable competing risk models were then built to predict the 10 year recurrence free probability (RFP), distant recurrence free probability (DRFP), overall survival (OS) and cancer specific mortality (CSM). All predictors of interest were added in the starting full models before selection, including age, gender, tumor site, clinical T stage, perineural invasion, margin status, pathologic N-status, and M-status. Stepdown method was used in model selection to choose predictive variables. An external dataset of 99 patients from 2 other institutions was used to validate the nomograms. Findings: Of 438 ACC patients, 27.2% (119/438) died from ACC and 38.8% (170/438) died of other causes. Median follow-up was 56 months (range 1–306). The nomogram for OS had 7 variables (age, gender, clinical T stage, tumor site, margin status, pathologic N-status and M-status) with a concordance index (CI) of 0.71. The nomogram for CSM had the same variables, except margin status, with a concordance index (CI) of 0.70. The nomogram for RFP had 7 variables (age, gender, clinical T stage, tumor site, margin status, pathologic N status and perineural invasion) (CI 0.66). The nomogram for DRFP had 6 variables (gender, clinical T stage, tumor site, pathologic N-status, perineural invasion and margin status) (CI 0.64). Concordance index for the external validation set were 0.76, 0.72, 0.67 and 0.70 respectively. Interpretation: Using an international collaborative database we have created the first nomograms which estimate outcome in individual patients with ACC. These predictive nomograms will facilitate patient counseling in terms of prognosis and subsequent clinical follow-up. They will also identify high risk patients who may benefit from clinical trials on new targeted therapies for patients with ACC. Funding: None. Highlights: Using the strength of international collaboration, we have created the first ever nomograms to predict outcomes in individual patients with ACC. These nomograms will allow physicians to better counsel patients on prognosis and identify patients at risk of recurrence. These nomograms will allow reliable stratification of patients to clinical trials evaluating new targeted therapies.